2018
DOI: 10.1093/milmed/usx071
|View full text |Cite
|
Sign up to set email alerts
|

Military-Tailored Yoga for Veterans with Post-traumatic Stress Disorder†

Abstract: Introduction: Among veterans of post-9/11 conflicts, estimates of post-traumatic stress disorder (PTSD) range from 9% shortly after returning from deployment to 31% a year after deployment. Clinical and pharmaceutically based treatments are underutilized. This could be due to concerns related to lost duty days, as well as PTSD patients’ fears of stigma of having a mental health condition. Yoga has been shown to reduce PTSD symptoms in the civilian population, but few studies have tested the impact of yoga on v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…18 It may also be useful to offer yoga interventions taught by older veterans, such as in Veteranto-Veteran programs, and veteran-specific resources available through VHA Whole Health program. 24,26,27 Researchers should consider interventions that address investigator reluctance to include older adults in clinical trials, including comorbidities, ageism, and practical barriers. 39 These considerations may be especially applicable now that research on the efficacy of yoga has matured and effectiveness studies are now needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 It may also be useful to offer yoga interventions taught by older veterans, such as in Veteranto-Veteran programs, and veteran-specific resources available through VHA Whole Health program. 24,26,27 Researchers should consider interventions that address investigator reluctance to include older adults in clinical trials, including comorbidities, ageism, and practical barriers. 39 These considerations may be especially applicable now that research on the efficacy of yoga has matured and effectiveness studies are now needed.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Yoga has been increasingly studied within the Veterans Health Administration (VHA) for treatment of posttraumatic stress disorder (PTSD) and has been found effective in reducing symptoms through the use of traumainformed and military-relevant instruction as well as a military veteran yoga teacher. [24][25][26] This work has not targeted older veterans or cancer survivors who may be more difficult to recruit into such programs, but who would nevertheless benefit.…”
mentioning
confidence: 99%
“…One study reported that yoga intervention effectively suppressed PTSD symptoms in OEF, OIF, and OND veterans. 84…”
Section: Methodsmentioning
confidence: 99%
“…These can include clinical treatments such as deep brain stimulation [ 25 ], noninvasive brain stimulation via repetitive transcranial magnetic stimulation, transcranial direct current stimulation [ 26 ], and neurofeedback [ 27 ]. Emerging therapies may also include cognitive-based conjoint therapy for PTSD [ 28 ], animal-assisted therapy [ 29 ], and yoga or mindfulness-based therapies [ 30 ]. In addition, given the high rates of comorbidities in individuals with PTSD, many approaches have incorporated the treatment of comorbidities to create new combination or adjunctive therapies for the treatment of PTSD [ 31 ].…”
Section: Introductionmentioning
confidence: 99%